2020
DOI: 10.7717/peerj.8750
|View full text |Cite
|
Sign up to set email alerts
|

Codon optimization, expression in Escherichia coli, and immunogenicity analysis of deformed wing virus (DWV) structural protein

Abstract: Background Deformed wing virus (DWV) is a serious threat to honey bees (Apis mellifera) and is considered a major cause of elevated losses of honey bee colonies. However, lack of information on the immunogenicity of DWV structural proteins has hindered the development of effective biocontrol drugs. Methods We optimized the VP1, VP2 and VP3 codons of DWV surface capsid protein genes on the basis of an Escherichia coli codon bias, and the optimized genes of roVP1, roVP2 and roVP3 were separately expressed in E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…The structural proteins consist of VP1, VP2, VP3, and VP4, of which VP1 is 44 kDa in size and is the largest capsid protein of all viruses in the order Picornavirales (Organtini et al, 2016). The size of VP2 (32 kDa) and VP3 (28 kDa) is similar to that of other picornavirus capsid proteins, and VP2 has been reported to exhibit good immunogenicity (Fei et al, 2020). Previous studies have shown that the structural proteins of Iflavirus are involved in viral invasion and replication (Brutscher et al, 2016;Kalynych et al, 2016;Procházková et al, 2018;Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The structural proteins consist of VP1, VP2, VP3, and VP4, of which VP1 is 44 kDa in size and is the largest capsid protein of all viruses in the order Picornavirales (Organtini et al, 2016). The size of VP2 (32 kDa) and VP3 (28 kDa) is similar to that of other picornavirus capsid proteins, and VP2 has been reported to exhibit good immunogenicity (Fei et al, 2020). Previous studies have shown that the structural proteins of Iflavirus are involved in viral invasion and replication (Brutscher et al, 2016;Kalynych et al, 2016;Procházková et al, 2018;Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%